Neuropeptide Kyotorphin (Tyrosyl-Arginine) has Decreased Levels in the Cerebro-Spinal Fluid of Alzheimer’s Disease Patients: Potential Diagnostic and Pharmacological Implications - Santos, Sara M.; Garcia-Nimo, Laura; Santos, Sónia S.; Tavares, Isaura; Cocho, José A.; Castanho, Miguel A. (Frontiers in Aging Neuroscience, 2013)
In Alzheimer’s disease (AD), besides the characteristic deterioration of memory, studies also point to a higher pain tolerance in spite of sensibility preservation. A change in the normal tau protein phosphorylation is also chracteristic of AD, which contributes to the pathogenesis of the disease and is useful in early diagnosis. Kyotorphin (KTP) is an endogenous analgesic dipeptide (Tyr-Arg) for which there is evidence of eventual neuroprotective and neuromodulatory properties. The objective of this work was to study the possible correlation between KTP and phosphorylated tau protein (p-Tau) levels in cerebro-spinal fluid (CSF) samples of AD patients. CSF samples were collected from 25 AD patients and 13 age-matched controls (N), where p-Tau and KTP levels were measured. We found a statistically significant difference between p-Tau/KTP values in AD and N groups with an inverse correlation between p-Tau and KTP values in AD samples.These results suggest that in the future KTP may be a candidate biomarker for neurodegeneration and may be a lead compound to be used pharmacologically for neuroprotection.